Virtualizing Lifemapper software infrastructure for biodiversity expedition. (26th April 2017) - Williams, Nadya; Stewart, Aimee; Papadopoulos, Phil
Summary: One of the activities of the Pacific Rim Applications and Grid Middleware Assembly (PRAGMA) is fostering Virtual Biodiversity Expeditions by bringing domain scientists and cyber infrastructure specialists together as a team. Over the past few years, PRAGMA members have been collaborating on virtualizing the Lifemapper software. Virtualization and cloud computing have introduced great flexibility and efficiency into IT projects. Virtualization refers to the technologies that provide a layer of abstraction between server hardware system and software that runs on it. This abstraction enables a logical view of computing resources and allows multiple servers to run on the same hardware. With this project, we are virtualizing Lifemapper by enabling its installation and configuration on a virtual cluster. Virtualization provides application scalability, maximizes resources utilization, and creates a more efficient, agile, and automated infrastructure. However, there are downsides to the complexity inherent in these environments, including the need for special techniques to deploy cluster hosts, dependence on virtual environments, and challenging application installation, management, and configuration. In this study, we report on progress of the Lifemapper virtualization framework focused on a reproducible and highly configurable infrastructure capable of fast deployment. Lifemapper is a distributed software application developed by the Biodiversity Institute at The University of Kansas. Lifemapper creates and maintains a publicly accessible archive of species distribution maps calculated from public specimen data. Lifemapper software also provides a suite of tools for biodiversity researchers that calculate single and multispecies distribution predictions and macroecological analyses through application programming interfaces. Our goal is to create a viable solution that can be easily adopted and reused by scientists from multiple institutions or projects. This solution (1) allows fast deployment of ready‐made cluster images, (2) reproduces the complete Lifemapper processing pipeline on demand at multiple sites and in different hosting environments, and (3) enables scientists to perform Lifemapper‐facilitated data processing on restricted‐use data, very large datasets, or other unique data. A key contribution of this work is describing the practical experience in taking a complex, clustered, domain‐specific, data analysis, and simulation system and enabling its operation on a variety of system configurations. Uses of this portability range from whole cluster replication to teaching and experimentation on a single laptop. System virtualization is used to practically define and make portable the full application stack, including all of its complex set of supporting software and allows Lifemapper deployment in a variety of environments.